Using Corpora in Language Teaching: Resources, Methods, and Evaluations (KULT_online, 2012)
This volume offers a selection of 17 papers presented at the seventh "Teaching and Language Corpora" Conference, which was held in Paris in 2006. The volume is divided into four parts that deal with new methods, research, applications, and evaluation of corpora and tools used in foreign language teaching. Some articles also include interdisciplinary approaches to using corpora in other fields as well as theoretical, corpus-linguistic concepts. This highly diverse selection of state of the art papers is of great interest to researchers and teachers alike and covers a variety of topics across the field of applied corpus linguistics.